Unstoppable the incredible power of faith in action - Vujicic, Nick (Waterbrook Press, 2012)
Millions around the world recognize the smiling face and inspirational messages of Nick Vujicic. Born without arms or legs, Nick has not allowed his physical challenges to keep him from enjoying great adventures, a fulfilling and meaningful career, and loving relationships. Nick has overcome trials and hardships by focusing on the promises that he was created for a unique and specific purpose, that his life has value and is a gift to others, and that even though he may endure hardships, God is always present and in control. Nick credits his success to the power that is unleashed when we put our faith into action.